A Class-V Myosin Required for Mating, Hyphal Growth, and Pathogenicity in the Dimorphic Plant Pathogen Ustilago maydis - Weber, Isabella (American Society of Plant Biologists, 2003)
In the early stages of plant infection, yeast-like haploid sporidia of Ustilago maydis respond to pheromone secreted by compatible partners by forming conjugation tubes. These then fuse to generate a dikaryotic hypha that forms appressoria to penetrate the host plant. As a first step toward understanding the structural requirements for these transitions, we have identified myo5, which encodes a class-V myosin. Analysis of conditional and null mutants revealed that Myo5 plays nonessential roles in cytokinesis and morphogenesis in sporidia and is required for hyphal morphology. Consistent with a role in morphogenesis, a functional green fluorescent protein–Myo5 fusion protein localized to the bud tip and the hyphal apex as well as to the septa and the spore wall during later stages of infection. However, the loss of Myo5 did not affect the tip growth of hyphae and sporidia. By contrast, Myo5 was indispensable for conjugation tube formation. Furthermore, myo5 mutants were impaired in the perception of pheromones, which indicates a particular importance of Myo5 in the mating process. Consequently, few mutant hyphae were formed that penetrated the plant epidermis but did not continue invasive growth. These results indicate a crucial role of Myo5 in the morphogenesis, dimorphic switch, and pathogenicity of U. maydis.